Politics Political Dynamics and Accountability of Regional Budgets in Creating Budget Transparency - M. Basuki Rahmat (ARISTO, 2021)
The article discusses the politics and accountability of regional budgets, which are used as an analysis in analyzing transparency, accountability and efficiency of regional finances. In this study, the authors used a qualitative approach with descriptive-critical methods with strength analysis and in the data processing using literature study. To discuss politics and accountability for local budgets, three conceptual frameworks are used. First, supervision to control and check the performance of regional governments in the implementation of regional autonomy and regional wealth management Strategies to improve local government performance. Second, the use of agencies as legal rules that are formulated indirectly by the government to carry out budget transparency by presenting data that will become one of the pillars in shaping public management. Illustrates that the legislature as an agent of government has the authority to take action by the executive. Third, a fiscal policy which aims to accelerate the country's economic activity, namely to increase economic growth. Where the fiscal policy executive to make a sustainable regional development plan. So that conclusion can be drawn that politics has an important role in creating transparency in regional financial budgets by involving the legislative and executive institutions. Where the legislative institution has a central role in discussing regional financial plans because it has the right to comb through budget items that are deemed less useful and give criticism to the executive if many of the proposed budget plans do not make sense or are prone to being a field of corruption. In addition,